2019
DOI: 10.1186/s13046-019-1283-z
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-486-3p functions as a tumor suppressor in oral cancer by targeting DDR1

Abstract: Background Discoidin domain receptor-1 (DDR1) tyrosine kinase is highly expressed in a variety of human cancers and involved in various steps of tumorigenesis. However, the precise mechanisms underlying the abnormal expression of DDR1 in oral squamous cell carcinoma (OSCC) has not been well investigated. Methods The expression of DDR1 on OSCC patients was determine by quantitative real-time PCR (qRT-PCR) and immunohistochemistry. Specific targeting by miRNAs was determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 58 publications
2
52
0
1
Order By: Relevance
“…Therefore, it is natural to speculate that miR‐451a, miR‐194‐5p, and miR‐486‐5p, which are significantly increased in the EVs of plasma from LUAD patients, may also be involved in the occurrence and development of LUAD. However, as previously reported , the expression of miR‐451a, miR‐194‐5p, and miR‐486‐5p was significantly downregulated in LUAD tissues compared to that in normal tissue in the TCGA database (Fig. S6).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Therefore, it is natural to speculate that miR‐451a, miR‐194‐5p, and miR‐486‐5p, which are significantly increased in the EVs of plasma from LUAD patients, may also be involved in the occurrence and development of LUAD. However, as previously reported , the expression of miR‐451a, miR‐194‐5p, and miR‐486‐5p was significantly downregulated in LUAD tissues compared to that in normal tissue in the TCGA database (Fig. S6).…”
Section: Discussionsupporting
confidence: 78%
“…S6). Several studies have confirmed that miR‐451a, miR‐194‐5p, and miR‐486‐5p might inhibit tumor cell growth by suppressing proliferation and invasion or promote apoptosis by targeting cancer‐associated genes . Recently, some studies found that tumor suppressor gene‐induced senescent cells modulate the immune response, which promotes the establishment of the inflammatory microenvironment that contributes to metastasis .…”
Section: Discussionmentioning
confidence: 99%
“…ChIP assay was performed based on previous described [24]. For miRNA treatment, OEC-M1 cells were treated with control mimics (NC, 20 nM), or miRNA mimics (PM-30a or PM-379, 20 nM) for 48 h. For chemical treatments, DOK cells were treatment with vehicle control (DMSO, 10 nM), arecoline (50 μM) or NNK (10 μM) for 5 days.…”
Section: Chromatin Immunoprecipitation (Chip)mentioning
confidence: 99%
“…Previously, we showed that DDR1 is one of the top five protein tyrosine kinases overexpressed in BQ-associated OSCC cell lines [29]; overexpression of DDR1 in OSCC tissues is statistically associated with three clinical features: angiolymphatic invasion (ALI), perineural invasion (PNI), and lymph node metastasis [30]. In the present study, we validated DDR1-associated collective cell invasion in OSCC tumor sections, and provided evidence that the small molecule inhibitor DDR1-IN-1 suppressed ALI in a mouse model with statistical significance.…”
Section: Of 18mentioning
confidence: 99%